Pola distribusi durian kura-kura (Durio testudinarius Becc.) di Kebun Raya Sambas Kalimantan Barat - Ferella, Elsa; Syamswisna, Syamswisna; Titin, Titin (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i01.p14, 2022)
Kebun Raya Sambas is a botanical garden in West Kalimantan. One of the plants endemic to the Borneo with the conservation status of Least Concern (LC) collected in the Kebun Raya Sambas is durian kura-kura ( Durio testudinarius Becc.). The information about Durio testudinarius Becc. in Indonesia is still limited by the lack of research on this species because it is difficult to get its existence as the cessation of primary forest in Borneo. The study was conducted in August 2021 to know the distribution pattern of Durio testudinarius Becc in Kebun Raya Sambas. The data were collected with 6 hectares of sampling area divided into six lines (transect) measuring 20 m x 500m. Species distribution patterns were analyzed by finding the index mortality (Id). Found 22 individual Durio testudinarius Becc in 4 lines of research. The results showed in 4 research lines that the distribution pattern of Durio testudinarius Becc was clustered with value Ip> 0. In addition, the results of the measurements of the environmental factors around Durio testudinarius Becc. that length is in the range of 28-32°C, air humidity 72-83%, soil temperature 25-27 °C, soil pH 6-6.5, and intensity of the light 777-7493 lux.